Investigation of the molecular epidemiology of HIV-1 in Khayelitsha, Cape Town, using serotyping and genotyping techniques - Jacobs, Graeme Brendon (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScMedSc (Pathology. Medical Virology))--University of Stellenbosch, 2005.